2023
DOI: 10.2147/opth.s423845
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Digital Ophthalmoscopes in Medicine

Rafael Robles,
Nikhil Patel,
Emily Neag
et al.

Abstract: Purpose Recent advances in telemedicine have led to increased use of digital ophthalmoscopes (DO) in clinical settings. This review aims to assess commercially available DOs, including smartphone (SP), desktop, and handheld ophthalmoscopes, and evaluate their applications. Methods A literature review was performed by searching PubMed (pubmed.ncbi.nlm.nih.gov), Web of Science (webofknowledge.com), and Science Direct (sciencedirect.com). All English-language papers that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Nevertheless, there are no international guidelines concerning DO usage, but the inclusion of those techniques should be considered [9]. There are different DOs, desktop-based DOs, handheld DOs, and smartphone-based retinal imaging DOs, and their sensitivity ranged from 61% to 81% between different studies considered in the most recent systematic review [10]. However, the NO BLIND study showed 100% specificity and 94.3% sensitivity for digital ophthalmoscope usage by ophthalmology specialists as compared to standard fundus oculi examination in mydriasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are no international guidelines concerning DO usage, but the inclusion of those techniques should be considered [9]. There are different DOs, desktop-based DOs, handheld DOs, and smartphone-based retinal imaging DOs, and their sensitivity ranged from 61% to 81% between different studies considered in the most recent systematic review [10]. However, the NO BLIND study showed 100% specificity and 94.3% sensitivity for digital ophthalmoscope usage by ophthalmology specialists as compared to standard fundus oculi examination in mydriasis [11].…”
Section: Introductionmentioning
confidence: 99%